Can CRP velocity in right iliac fossa pain identify patients for intervention? A prospective observational cohort study. Issue 5 (October 2019) - March, Brayden; Leigh, Lucy; Brussius-Coelho, Marcio; Holmes, Merran; Pockney, Peter; Gani, Jon
Abstract: Introduction: Previous studies have shown single CRP measurements at time of presentation to have limited predictive benefit for appendicitis. Our objective was to determine the diagnostic utility of serial CRP measurements (to determine CRP velocity [CRPv]) in patients with right iliac fossa (RIF) pain. Methods: A single-centre prospective observational study was conducted on adult patients admitted with RIF pain. CRP was measured on admission, at midnight, and the following morning. Appendicitis was diagnosed on histopathology, or diagnostic imaging in non-operatively managed patients. Therapeutic interventions included all appropriate operative procedures and effective non-operative treatment with antibiotics. Logistic regression was used to generate predictors of therapeutic intervention, and then used to create a new risk score incorporating CRPv. Results: 98 of 112 (87.5%) participants had complete CRP data. 58 patients met the criteria for appendicitis (59.2%). Most patients presented with intermediate Modified Alvarado Scores (MAS) 5–6 (40.8%) or Appendicitis Inflammatory Response Scores (AIRS) 5–8 (49%). Our risk score had an AUROC of 0.88 (95% CI 0.81–0.96) in predicting therapeutic intervention. This score was superior to MAS, AIRS, and single admission biomarker measurements. Patients with an increasing CRPv had 14 times the odds (OR 14.07, 95% CI 0.63–315.2) of complicated appendicitis, and no cases of complicated appendicitis were observed in patients with a flat CRPv. Conclusions: CRP velocity is superior to single CRP at predicting intervention. Our v-Score shows promise as a decision making-aide by predicting the need for surgical intervention in RIF pain. A flat CRPv identifies a group of patients with a very low risk of complicated appendicitis.